2022
DOI: 10.3390/foods11142086
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Total Soluble Solids and pH of Strawberry Fruits Using RGB, HSV and HSL Colour Spaces and Machine Learning Models

Abstract: Determination of internal qualities such as total soluble solids (TSS) and pH is a paramount concern in strawberry cultivation. Therefore, the main objective of the current study was to develop a non-destructive approach with machine learning algorithms for predicting TSS and pH of strawberries. Six hundred samples (100 samples in each ripening stage) in six ripening stages were collected randomly for measuring the biometrical characteristics, i.e., length, diameters, weight and TSS and pH values. An image of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 84 publications
0
9
0
1
Order By: Relevance
“…The maturity level of the strawberry was categorized based on the amount of redness on the strawberry. In the study, Basak et al [15] categorized the maturity level of strawberries according to different growth stages: whiting, turning red, three-quarter red, bright red, and dark red. In reference to that study, the ripeness level of strawberries was categorized as white-green to green as immature, turning red up to three-quarter red as transition, and above three-quarters red to dark red as mature.…”
Section: Plant Materials and Image Acquisitionmentioning
confidence: 99%
“…The maturity level of the strawberry was categorized based on the amount of redness on the strawberry. In the study, Basak et al [15] categorized the maturity level of strawberries according to different growth stages: whiting, turning red, three-quarter red, bright red, and dark red. In reference to that study, the ripeness level of strawberries was categorized as white-green to green as immature, turning red up to three-quarter red as transition, and above three-quarters red to dark red as mature.…”
Section: Plant Materials and Image Acquisitionmentioning
confidence: 99%
“…Basak et al. [ 21 ] developed a non-destructive method using ML algorithms to predict the total soluble solids (TSS) and pH of strawberries. Image processing techniques have also been used in several studies to assess food quality.…”
Section: Relevant Workmentioning
confidence: 99%
“…The RGB, HSV, and HSL color-space channels were used as input variables to develop multiple linear regression (MLR) and support vector machine regression (SVM-R) models. The results demonstrated that an SVM-R model working on the characteristics in the HSV color space performed better than an MLR model for total soluble solids and pH prediction (accuracy of 84.1% and 79.2% for total soluble solids and 78.8% and 72.6% for pH in the training and testing stages, respectively) [ 174 ].…”
Section: Innovative Non-destructive Techniques For the Quality Monito...mentioning
confidence: 99%